2017
DOI: 10.15252/embj.201796823
|View full text |Cite
|
Sign up to set email alerts
|

KTN80 confers precision to microtubule severing by specific targeting of katanin complexes in plant cells

Abstract: The microtubule (MT)-severing enzyme katanin triggers dynamic reorientation of cortical MT arrays that play crucial functions during plant cell morphogenesis, such as cell elongation, cell wall biosynthesis, and hormonal signaling. MT severing specifically occurs at crossover or branching nucleation sites in living cells. This differs from the random severing observed along the entire length of single MTs and strongly suggests that a precise control mechanism must exist However, how katanin senses and cleaves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
60
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(72 citation statements)
references
References 49 publications
5
60
1
Order By: Relevance
“…We therefore focused on the microtubule severing protein complex KATANIN (KTN), which is important for secondary wall production and microtubule alignment (Burk et al 2001; Stoppin-Mellet et al 2007). The KTN complex is a hexamer of KTN1-KTN80 heterodimers (Wang et al 2017). The single copy of KTN1 is responsible for microtubule severing whereas four KTN80 isoforms confer targeting to microtubule crossovers.…”
Section: Resultsmentioning
confidence: 99%
“…We therefore focused on the microtubule severing protein complex KATANIN (KTN), which is important for secondary wall production and microtubule alignment (Burk et al 2001; Stoppin-Mellet et al 2007). The KTN complex is a hexamer of KTN1-KTN80 heterodimers (Wang et al 2017). The single copy of KTN1 is responsible for microtubule severing whereas four KTN80 isoforms confer targeting to microtubule crossovers.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we reported that the augmin complex recruits the g-tubulin complex to preexisting microtubules and initiates microtubule nucleation [7]. Moreover, we described how an intricate interaction between the katanin p60 subunit KTN1 and the p80 subunit KTN80 confers precise microtubule severing at either microtubule branching nucleation sites or crossovers [8]. Here, we observed that augmin preferentially localizes to microtubule crossovers.…”
mentioning
confidence: 53%
“…Another example involves four loci encoding katanin p80 subunits ( KTN80.1 , KTN80.2 , KTN80.3 , and KTN80.4 ) in Arabidopsis . We designed three sgRNAs to simultaneously knockout all four KTN80 genes using CRISPR/Cas9 . The resulting quadruple mutant exhibited a severe dwarf phenotype, demonstrating that the four KTN80s act redundantly and providing genetic insight into the function of KTN80s during development in vivo.…”
Section: Crispr/cas9‐created Mutations In Plantsmentioning
confidence: 99%